Guide des archives judiciaires de Montréal - Beaudin, François (Archives, 1970)
Keywords: Archives

Les archives de l'Assemblée nationale du Québec - Bernier, Gaston (Archives, 2004)
Keywords: Archives

Les archives de la ville de Montréal - Gérin-Lajoie, Henri (Archives, 1969)
Keywords: Archives municipales

Bref aperçu des archives du port de Montréal - Brouillard, Pierre (Archives, 1976)
Keywords: Archives; Port

Les archives photographiques à la Ville de Montréal - Robert, Mario (Archives, 1996)
Keywords: Archives municipales; Photographie

Guide des sources d'archives concernant la médecine sur l'île de Montréal, des débuts jusqu'en 1900 - Janson, Gilles; Lalonde, Michel (Archives, 1980)
Keywords: Archives; Médecine

Les archives en milieu muséal: le cas du Musée McCord - Cartier, François (Archives, 2005)
Keywords: Archives; Musée McCord; Musées

Utilisation des archives dans la cause de canonisation de Marguerite Bourgeoys - De 1972 à 1982 - Tremblay, Hélène (Archives, 1985)
Keywords: Archives; Bourgeoys, Marguerite; Communautés religieuses; Congrégation de Notre-Dame

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

L’archive littéraire à la rescousse de l’histoire: le cas des Comédies du Statu quo (1834) - Desjardins, Nancy (Archives et fabrique du textile littéraire, 2001)
Keywords: Archives; Papineau, Louis-Joseph; Rébellions

Informatiser un répertoire d'archives photographiques: l'exemple de l'atelier d'histoire Hochelaga-Maisonneuve - Desbiens, Édith; Massicotte, Daniel (Archives, 1993)
Keywords: Archives; Atelier d'histoire d'Hochelaga-Maisonneuve; Hochelaga (quartier); Maisonneuve (quartier); Photographie; Quartiers

The History of the Montreal Jewish Public Library and Archives - Miller, Evelyn (The Canadian Archivist / L'archiviste canadien, 1970)
Keywords: Archives; Jewish Public Library; Juifs

Papiers Duvernay conservés aux Archives de la province de Québec - Caron, Ivanhoé (Rapport de l'archiviste de la province de Québec, 1926)
Keywords: Archives; Duvernay, Ludger; Imprimerie

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Archives religieuses: guide sommaire - Forget, André; Hémond, Robert (Cahiers du Regroupement des archivistes religieux, 1992)
Keywords: Archives; Églises

Le patrimoine archivistique religieux. Une source indispensable pour comprendre l'histoire du Québec - Lamothe, Madelaine; Drouin, François; Virr, Richard; Stanley, Susan (Archives, 1992)
Keywords: Archives

Les archives judiciaires de Montréal - Massicotte, E.-Z. (Bulletin des recherches historiques, 1926)
Keywords: Archives

Les archives industrielles au Québec: un guide sommaire - St-Georges, Lise (Association québécoise pour le patrimoine industriel, 1995)
Keywords: Archives

Révolution dans les archives...et dans la reconstitution du passé - Deslandres, Dominique (Les cahiers des Dix, 2023)
Keywords: Archives

Les archives municipales de la ville de Montréal - Gérin-Lajoie, Henri (Urban History Review / Revue d'histoire urbaine, 1974)
Keywords: Archives; Archives municipales

L’ère des archives québécoises sur le Web - Robert, Mario (Cap-aux-Diamants, 2014)
Keywords: Archives; Archives municipales

Répertoire du fonds François Déziel, FN-0664 - Lalancette, Christian; Archives du Séminaire de Trois-Rivières. (Archives du Séminaire de Trois-Rivières, 2000)
Keywords: Peinture

Les archives du transport à Montréal - Pélissier, Denise (Archives, 1977)

La commission de police de Montréal (1840-1910) & les archives du Québec - Cournez, Severine (Université d'Angers, 1996)
Keywords: Archives; Police

Les procès en sorcellerie, des archives longtemps négligées : le cas de Montréal - Pettigrew, Stéphanie (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Archives; Tribunaux

Étude sur la création d'un secteur d'archives télévisuelles à la Cinémathèque québécoise - Laurendeau, Jean-Pierre (Ministère de la Culture et des Communications, 1994)
Keywords: Archives; Cinéma

Histoire et inventaire du fonds d'archives du chœur de la Cathédrale de Montréal - Larose, Anik (Université de Montréal, 1991)
Keywords: Archives; Cathédrale

Bref aperçu sur l'histoire des archives de la chancellerie de l'archevêché de Montréal - Beaudin, François (La Société canadienne d'histoire de l'Église catholique, 1964)
Keywords: Archevêché; Archives

''Au-delà du syndrome de la «citation payante»'': les archives vivantes et la recherche réciproque en histoire orale - High, Steven (Revue d'histoire de l'Amérique française, 2015)
Keywords: Archives; Histoire

La revue Archives à travers ses vingt dernières années d’existence, 1988-2008 - Gagnon-Arguin, Louis (Archives, 2009)

Les archives de l'Institut Canadien de Montréal (1844-1900) - historique et inventaire - Lamonde, Yvan (Revue d'histoire de l'Amérique française, 1974)
Keywords: Archives; Institut canadien

Les archives du Musée McCord / The McCord Museum Archives - Miller, Pamela (Musée McCord d'histoire canadienne, 1992)
Keywords: Archives; Musée McCord; Musées

Les archives du réseau institutionnel canadien-français conservées au Québec et à Ottawa, 1834-1973 - Dumas, François; Garon, Louis; Léveillé, Marie (Archives, 2004)

Conservation des archives de certaines entreprises de Montréal. Un aperçu du secteur privé vu de l'extérieur de Montréal - Rider, Peter (Archives, 1979)

L'odyssée des archives de la Société Historique de Montréal - Robert, Mario (Montréal en tête, 2019)
Keywords: Archives; Société historique de Montréal

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

État général des fonds d'archives et collections du Centre de recherche Lionel-Groulx - Saint-Hilaire, Danielle; Rémillard, Juliette (Le Centre, 1987)
Keywords: Archives; Centre de recherche Lionel-Groulx

Catalogue de la bibliothèque administrative des archives municipales et inventaire chronologique des cartes et plans de Montréal, 1534-1918 (s.é., 1918)
Keywords: Archives municipales; Cartes et plans

La nuit de feu des livres et des archives du Parlement - Gallichan, Gilles (Bulletin d'histoire politique, 2013)
Keywords: Archives; Incendies; Parlement; Torys; Émeutes

L’archive et l’invention littéraire: le cas des Mystères de Montréal d’Auguste Fortier (1893) - Ducharme, Nathalie (Archives et fabrique du textile littéraire, 2001)

Le traitement du fonds de l'Association générale des étudiants de l'Université de Montréal (AGEUM) - Barriault, Jeannine; Chouinard, Denys (Archives, 1985)
Keywords: Archives; Association générale des étudiants de l'Université de Montréal; Université de Montréal; Étudiants

Les archives de la Société historique de Montréal. La contribution de la Société historique de Montréal à la sauvegarde du patrimoine archivistique montréalais - Lebeau, Mireille (Montréal en tête, 2008)
Keywords: Archives; Conservation; Histoire; Patrimoine; Société historique de Montréal

Historique des archives de l'Hôtel-Dieu de Montréal et les hospitalières de Saint-Joseph - Ducharme, Jacques (L'Hôtel-Dieu de Montréal, 1973)
Keywords: Archives; Communautés religieuses; Hospitalières de Saint-Joseph; Hôpitaux; Hôtel-Dieu

Scrapbooks in the McGill University Archives, 1843-1969 - Sparks, Ann (Archives de l'Université McGill, 1971)
Keywords: Université McGill

Inventaire des actes de foi et hommage conservés aux Archives judiciaires de Montréal - Massicotte, E.-Z. (Rapport de l'archiviste de la province de Québec, 1921)
Keywords: Seigneurie

Répertoire des engagements pour l'ouest conservés dans les archives judiciaires de Montréal - Massicotte, E.-Z. (Rapport de l'archiviste de la province de Québec, 1933)
Keywords: Engagés; Fourrure

En marge de la canonisation de Marguerite Bourgeoys du 31 octobre 1982: dépôt d'archives de la congrégation de Notre-Dame à Montréal (Bulletin de l'Association des archivistes de France, 1983)
Keywords: Bourgeoys, Marguerite; Communautés religieuses; Congrégation de Notre-Dame

Guide to Archival Ressources at McGill University / Guide des sources d'archives à l'Université McGill - Caya, Marcel (Archives de l'Université McGill, 1985)
Keywords: Université McGill

A Preliminary List of Papers Transferred to the McGill University Archives by the Secretary-General, Accession No. 1766 - Kense, Françoise; Kuplowsky, Walter (Archives de l'Université McGill, 1974)
Keywords: Université McGill

Inventaire des archives du Comité des professeurs (P61) - Bouchard, Isabella (Université de Montréal, Service des archives, 1979)
Keywords: Enseignants; Université de Montréal

A Preliminary Guide to the Records of the Montreal General Hospital Deposited in McGill University Archives - Accession No 1501 - 1818-1972 - Andreassen, John C. L. (Archives de l'Université McGill, 1972)
Keywords: Hôpitaux; Montreal General Hospital

Supplement to a Preliminary Guide to the Records of the Montreal General Hospital (School of Nursing) Deposited in the McGill University Archives, Accession no. 1501 (Archives de l'Université McGill, 1975)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 3 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession No. 1501/200-416 - Noel, Marcellin (Archives de l'Université McGill, 1974)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 2 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession Number 1501/174-199 - Andreassen, John C. L. (Archives de l'Université McGill, 1973)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 4 and 5 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession No. 1501/417-466 - Noel, Marcellin (Archives de l'Université McGill, 1974)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 1 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession No 1501/83 to 1501/173 - Andreassen, John C. L. (Archives de l'Université McGill, 1973)
Keywords: Hôpitaux; Montreal General Hospital

État général des fonds d'archives de l'École polytechnique de Montréal - Dessureault, Louis-René; Trépanier, Lynne; Lavigne, Pierre (École polytechnique, Direction générale, Section des archives, 1989)
Keywords: École polytechnique

Guide des fonds d'archives privées conservées au Service des archives de l'UQAM - Janson, Gilles; Pilote, Francine; Cadieux, Anne-Marie (Université du Québec à Montréal, Service des archives, 1986)
Keywords: Université du Québec à Montréal

Guide aux archives des églises locales, Synode Montréal/Ottawa, Église unie du Canada / Guide to the Local Church Records, Montreal/Ottawa Conference, United Chruch of Canada - Stanley, Susan (Montreal/Ottawa Conference Archives Committee, United Church of Canada, 1986)
Keywords: Protestants; Église Unie

Fonds Ernest-Cormier - Fortier, Robert (Les chemins de la mémoire. Biens mobiliers du Québec, 1999)
Keywords: Archives

L'archivistique au Québec depuis 1960: une profession et une discipline en émergence - Gagnon-Arguin, Louise (Université Laval, 1990)
Keywords: Archives; Archives municipales

Fonds Jacques-Ferron - Olscamp, Marcel (Les chemins de la mémoire. Biens mobiliers du Québec, 1999)
Keywords: Archives; Écrivain

Mère Émilie Gamelin, fondatrice des Soeurs de la Providence - Frigon, Thérèse (Archives, 1985)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier, Émilie (Gamelin, Émilie)

Un recensement et son recenseur: le cas de Montréal en 1825 - Linteau, Paul-André; Robert, Jean-Claude (Archives, 1976)
Keywords: Maires; Recensements; Viger, Jacques

Conrad Poirier, photographe, 1913-1968 - Provost, Anne (Archives, 1978)
Keywords: Photographie; Poirier, Conrad

Le fonds Ernest Cormier - Lalonde, Michel (Archives, 1984)
Keywords: Cormier, Ernest; Ingénieurs

L’apport de François Beaudin: la mise en place du rapport Deschênes - Baillargeon, Diane (Archives, 2017)
Keywords: Université de Montréal

Théâtre à Montréal, 1825-1930: un récit visuel mettant en scène des documents patrimoniaux - Léger, Danielle (Archives, 2019)
Keywords: Cartes et plans; Histoire; Patrimoine; Théâtre

Vivre Montréal, 1920-1969 - Fontaine, Julie; Lebeau, Mireille; Robert, Mario (Aux limites de la mémoire, 2011)
Keywords: Archives municipales; Photographie

Guide des archives Barreau du Québec - Barreau du Québec (Service de la gestion de l'information, 2003)
Keywords: Barreau; Droit

Les archives du port de Montréal - Brouillard, Pierre (Rapport et travaux 1973-1975, 1975)
Keywords: Port

Index des archivistes / généalogistes de famille - Dupuis, Gaston L.; DaPrato, Micheline; Fortin, Francine (G.L. Dupuis, 1993)

Inventaire d'archives - Archives de la Chancellerie de l'Archevêché de Montréal - Instruments de recherche 1877-1896 - Beaudin, François (Revue d'histoire de l'Amérique française, 1970)
Keywords: Archevêché

Guide des Archives conservées à la CSN - Charbonneau, Hélène (Confédération des syndicats nationaux, Service de la documentation, 1989)
Keywords: Confédération des syndicats nationaux

Photographes et archives photographiques des quartiers disparus - Robert, Mario (Quartiers disparus: Red Light, Faubourg à M'lasse, Goose Village, 2014)
Keywords: Photographie; Quartiers

Guide des archives des unions internationales à Montréal - Cardin, Jean-François; Rouillard, Jacques (Université de Montréal, Département d'histoire, 1987)
Keywords: Syndicats internationaux

Hochelaga-Maisonneuve: répertoire des archives photographiques: 1880-1960 - Atelier d'histoire Hochelaga-Maisonneuve; Desbiens, Édith; Massicotte, Daniel; Otis, Yves (Atelier d'histoire Hochelaga-Maisonneuve, 1993)
Keywords: Hochelaga (quartier); Maisonneuve (quartier); Photographie; Quartiers

Guide sommaire des archives des diocèses catholiques au Canada / Abridged Guide to the Archives of Catholic Dioceses in Canada (Université Saint-Paul, 1981)
Keywords: Diocèse

Historienne, mentore, libre-penseuse: réflexions autour de l'oeuvre d'Andrée Lévesque - Fahrni, Magda (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Archives; Femmes; Histoire

Inventaire des archives conciliaires du Fonds Paul-Émile Léger - Lafontaine, Pierre (Éditions des Partenaires, 1995)
Keywords: Archevêché; Léger, Paul-Émile

Quand les archives racontent Montréal - 100 pièces d'exceptions - Bednarz, Nicolas; Forest-Bonin, Anick; Robert, Mario (Publication du Québec et Ville de Montréal, 2013)

Des archives de femmes pour le début du siècle - Pinard, Yolande (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1976)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Local Council of Women

Guide chronologique des archives relatives à l'histoire de l'Université de Montréal conservées au Service des archives de l'Université de Montréal - Plante, Denis (Université de Montréal, Le Service, 1988)
Keywords: Université de Montréal

Que reste-t-il… des archives de nos premières émissions? - Moreau, Jean-Paul (Cap-aux-Diamants, 2002)
Keywords: Télévision

Inventaire sommaire des archives de la Société historique de Montréal - Nish, Cameron (Centre d'étude du Québec, Sir George William University, 1969)
Keywords: Société historique de Montréal

La génération de la Conquête: un questionnement de l’archive - Andrès, Bernard (Voix et Images, 1995)
Keywords: Histoire; Écrivains

Les archives de la Chancellerie de l'archevêché de Montréal - Beaudin, François (Association des bibliothèques de langue française - Bulletin, 1969)
Keywords: Archevêché

Photogenic Montreal: Activisms and Archives in a Post-Industrial City - Langford, Martha; Sloan, Johanne (McGill-Queen's / Beaverbrook Canadian Foundation Studies in Art History Series, 2021)
Keywords: Conservation; Patrimoine; Photographie; Quartiers

The Christian Pavilion at Expo 67: Notes from Charles Gagnon's Archive - Kin Gagnon, Monika (Expo 67: Not Just a Souvenir, 2010)
Keywords: Cinéma; Expositions

Bibliographie de l'île Jésus suivie d'un inventaire d'archives - Dionne, André (Institut québécois de recherche sur la culture, 1983)
Keywords: Île Jésus

From the Archives: the Montreal Gazette on Music from 1786 to 1797 - Kallmann, Helmut (Canadian Music Journal, 1962)
Keywords: Montreal Gazette; Musique

Notre-Dame-des-Neiges: ce que révèlent les archives de pierre - Dandavino, Rita Rachele (Continuité, 1991)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière)

L'honneur féminin à Montréal à travers les archives judiciaires (1698-1756) - Dufresne, Amélie (Université de Montréal, 2021)
Keywords: Criminalité; Femmes

Documents sur les anciennes cures de Montréal aux archives du Séminaire de Québec - Provost, Honorius (La Société canadienne d'histoire de l'Église catholique, 1946)

The Largest Bulk of Minute Deeds of a Single Notary in Montreal Archives - Lefebvre, Jean-Jacques (Revue du notariat, 1962)
Keywords: Griffin, Frederick; Griffin, Henry; Griffin, John Carr; Griffin, Robert; Notaires

Boxing Time: Landscape, Feminism and the Archive in Selected Works by Angela Grauerholz - Brock, Lesley L. (Université Concordia, 2004)
Keywords: Paysages; Photographie

Inventaire des marchés de construction des Archives nationales du Québec à Montréal, 1800-1830 - Giroux, André (Parcs Canada, 1981)

Les archives d’enquêtes sur l’éducation au Bas-Canada. Leur contenu et leur utilisation possible - Dufour, Andrée (L'école en chiffres? Réflexions sur les statistiques scolaires au Québec, XIXe-XXe siècles, 2006)

Index des contrats de mariage conservés dans les archives judiciaires du district de Montréal (1693-1843) - Massicotte, E.-Z. (s.é.)

Arrêts, Edits, Ordonnances, Mandements et Règlements Conservés dans les Archives du Palais de Justice de Montréal - Massicotte, E.-Z. (Mémoires et comptes rendus de la Société royale du Canada, 1917)
Keywords: Palais de justice

Inventaire général des registres des archives de la Chancellerie de l'Archevêché de Montréal, 1643-1876 - Beaudin, François (Revue d'histoire de l'Amérique française, 1967)
Keywords: Archevêché; Registres

Identities, Communities, and the Infrastructures of History: Creating Canadian Jewish Archives in the 1930s and the 1970s - Menkis, Richard (History, Memory, And Jewish Identity, 2015)
Keywords: Congrès juif canadien; Histoire; Juifs

Inventaire analytique des documents de la période 1600-1760 - Archives de la Chancellerie de l'Archevêché de Montréal (ACAM) - Beaudin, François (Revue d'histoire de l'Amérique française, 1966)
Keywords: Archevêché

Le patrimoine documentaire de la paroisse Saint-Enfant-Jésus de la Pointe-aux-Trembles depuis 1669: un trésor d'archives - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles, 2013)
Keywords: Pointe-aux-Trembles

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Keywords: Danse; Femmes; Histoire; Musicien; Musique

Westmount public library: Celebrating 125 years (The Westmount Historian, 2024)
Keywords: Archives; Patrimoine; Vitraux; Westmount

Regards sur une Bible hébraïque, une Bible polyglotte et une Bible de Genève conservées par Bibliothèque et Archives nationales du Québec - Crevier Denommé, Isabelle (Ouvrages phares de la Réforme & de la Contre-Réforme dans les collections montréalaises, 2014)
Keywords: Bibliothèque nationale

Voix des esclaves autochtones et des esclavagistes: un cas d’histoire intersectionnelle dans les archives judiciaires de la juridiction de Montréal - Deslandres, Dominique (Les Cahiers des Dix, 2018)
Keywords: Autochtones; Esclaves

Inventaire général des dossiers des archives de la Chancellerie de l'Archevêché de Montréal de l'année 1600 à l'année 1876 - Beaudin, Francois (Revue d'histoire de l'Amérique française, 1966)
Keywords: Archevêché

Folie, norme et rôles sexuels au Québec dans la seconde moitié du XIXe siècle: quelques observations tirées des archives de la curatelle - Cellard, André (Revue d'histoire de l'Amérique française, 2008)

Femmes devant le tribunal du roi : la culture judiciaire des appelantes dans les archives de la juridiction royale de Montréal (1693-1760) - Deslandres, Dominique (Les Cahiers des Dix, 2017)
Keywords: Criminalité; Esclaves; Femmes; Tribunaux

Guide pour l'étude d'entreprises montréalaises et leurs archives avant 1947 / A Guide to the History and Records of Selected Montreal Business Before 1947 - Sweeny, Robert (Université McGill, Montreal Business History Project, 1979)

Images du danger dans les archives judiciaires. Comprendre la violence et le vagabondage dans un centre urbain du début du XIXe siècle, Montréal (1820-1842) - Poutanen, Mary Anne (Revue d'histoire de l'Amérique française, 2002)
Keywords: Délinquance; Itinérance

Reading the Multimedia Archive Surrounding Montreal's Post-War LGBTQ Bars: A Genealogical Return to Madame Arthur and Il était une fois dans l'Est - Pidduck, Julianne (Quebec Studies, 2015)
Keywords: Alcool

Montréal sous le régime français. Répertoire des arrêts, édits, mandements, ordonnances et règlements conservés dans les archives du Palais de justice de Montréal, 1640-1760 - Massicotte, É.-Z. (G. Ducharme, 1919)
Keywords: Palais de justice

À la découverte du Fonds Albéric Bourgeois (1876-1962): thématiques d'une société en transformation, 1899-1957 - Hardy, Dominic; Godin-Laverdière, Julie-Anne; Perron, Nancy (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Archives; Bourgeois, Albéric; Caricature; Histoire

Une “vaillante phalange” contre “vieux pontifes”. La réception des Soirées du Château de Ramezay dans le journal Les Débats - Cellard, Karine (Archives et fabrique du textile littéraire, 2001)
Keywords: Ramezay (château de)

Pectus est quod disertos facit: éloquence et sublime dans la Rhétorique (1796) de Jacques-Antoine Houdet - Bélanger, Anne; Landry, Alexandre (Archives et fabrique du textile littéraire, 2001)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

Ironie, sarcasme et dérision dans Le Canadien (1806-1810) - Laquerre, Marie-Lise; Massé, Stéphanie (Archives et fabrique du textile littéraire, 2001)
Keywords: Humour

Étude de mise en valeur du séminaire de Saint-Sulpice. Volume 4: Annexes - Des Rochers, Jacques (Prêtres de Saint-Sulpice, Ministère de la Culture et des Communications, Direction de Montréal, Fondation du patrimoine religieux et Patrimoine canadien, 1998)
Keywords: Archives; Communautés religieuses; Patrimoine; Sulpiciens; Séminaire

Les quartiers municipaux de Montréal depuis 1832 (Archives municipales, 1973)
Keywords: Quartiers

Montréal, historique de ses quartiers municipaux - Gauthier, Paul; Gérin-Lajoie, Henri (Archives municipales, 1965)
Keywords: Quartiers

L'école Saint-Stanislas supérieure et secondaire 1929-1977: l'esprit en mouvement de plusieurs générations - Moineau, Guy; Laprotte, Jean (Archives F.I.C., 2015)

Étude de mise en valeur du séminaire de Saint-Sulpice. Volume 1: Les fonds et les collections - Des Rochers, Jacques (Prêtres de Saint-Sulpice, Ministère de la Culture et des Communications, Direction de Montréal, Fondation du patrimoine religieux et Patrimoine Canadien, 1998)
Keywords: Archives; Bibliothèque Saint-Sulpice; Communautés religieuses; Patrimoine; Sulpiciens; Séminaire

Étude de mise en valeur du séminaire de Saint-Sulpice. Volume 2: Les bâtiments, les cours et le jardin - Des Rochers, Jacques (Prêtres de Saint-Sulpice, Ministère de la Culture et des Communications, Direction de Montréal, Fondation du patrimoine religieux et Patrimoine canadien, 1998)
Keywords: Archives; Archéologie; Communautés religieuses; Jardins; Patrimoine; Sulpiciens; Séminaire

Inventaire analytique de la correspondance de Mgr Ignace Bourget pour l'année 1848 - Pouliot, Léon; Beaudin, François (Rapport des Archives du Québec, 1967)
Keywords: Bourget, Ignace; Évêques

Inventaire analytique de la correspondance de Mgr Ignace Bourget pour les années 1849 et 1850 - Pouliot, Léon; Beaudin, François (Rapport des Archives du Québec, 1969)
Keywords: Bourget, Ignace; Évêques

Inventaire analytique de la correspondance de Mgr Ignace Bourget pour 1846 - Pouliot, Léon (Rapport des Archives du Québec, 1965)
Keywords: Bourget, Ignace; Évêques

La coiffure dans la région montréalaise - Séguin, Robert-Lionel (Rapport des Archives du Québec, 1963)

Collection Lionel-Groulx - Institut d'histoire de l'Amérique française (Les chemins de la mémoire. Biens mobiliers du Québec, 1999)
Keywords: Archives; Desjardins, Alphonse; Desrosiers, Léo-Paul; Groulx, Lionel; Histoire; Laurendeau, André

C'était mon frère... Supplément I, 1965-1976 - Saint-Pierre, Bertrand; Poirier, Léandre (Archives des Franciscains, 1976)
Keywords: Communautés religieuses; Franciscains

Étude de mise en valeur du séminaire de Saint-Sulpice. Volume 3: Abrégé - Des Rochers, Jacques (Prêtres de Saint-Sulpice, Ministère de la Culture et des Communications, Direction de Montréal, Fondation du patrimoine religieux et Patrimoine canadien, 1999)
Keywords: Archives; Archéologie; Bibliothèque Saint-Sulpice; Communautés religieuses; Jardins; Patrimoine; Sulpiciens; Séminaire

Regards catholiques sur les villes québécoises: une haine à géométrie variable (1918-1939) - Bérubé, Harold (Archives de sciences sociales des religions, 2014)

The Pastness of Allô Police - Straw, Will (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Criminalité; Photographie

Erase and See: The Photogénie of a Metropolis in Progress - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Paysages; Photographie

Architecture, Photography, and Power: Picturing Montreal, 1973-74 - Imogen Hammond, Cynthia (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; McConnell, John Wilson; McConnell, John Wilson (maison); Patrimoine; Photographie; Shaughnessy (maison); Van Horne (maison); Van Horne, William

Through the Lens of Edith Mather: Photographing Demolition and the Transforming City - Southcott, Tanya (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; Femmes; Patrimoine; Photographie; Rues

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

Le Royal Victoria Hospital et l'instauration du régime d'assurance-maladie québécois 1965-1971 - Charpentier, Alix (Université d'Angers, 2003)
Keywords: Assurance; Hôpitaux; Royal Victoria Hospital

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Les guides touristiques d’hôtels montréalais, 1857-1917 – Une stratégie publicitaire - Lefebvre, Michèle (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Publicité; Tourisme

Aptitude à signer et usage de la signature chez les ouvriers du bâtiment à Montréal, 1700-1750 - Latouche, Pierre-Édouard (Revue de Bibliothèque et Archives nationale du Québec, 2009)

l'Institut canadien de Montréal: un avant-goût des grands principes de la bibliothèque publique moderne - Lefebvre, Michèle (Revue de Bibliothèque et Archives nationale du Québec, 2010)
Keywords: Institut canadien

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

Du journal à l'oeuvre « Écrire, mon secret, ma captivité, ma vie », Yves Navarre - Lannegrand, Sylvie (Revue de Bibliothèque et Archives nationale du Québec, 2011)
Keywords: Écrivains

Genèse du cycle de « La batèche » de Gaston Miron: de la noirceur aux rives de l'aube nouvelle - Villeneuve, Karine (Revue de Bibliothèque et Archives nationale du Québec, 2011)
Keywords: Miron, Gaston; Poésie

La Revue populaire et Le Samedi – Objets de diffusion de la modernité photographique au Québec, 1935-1945 - Tousigant, Zoë (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie

Montréal érotique : pin-up et imagerie de nus chez le photographe de presse Conrad Poirier, 1912-1968 - Godin-Laverdière, Julie-Anne (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie; Poirier, Conrad

Les passerelles internationales de la maison d'édition Parti pris - Fabre, Gérard (Revue de Bibliothèque et Archives nationale du Québec, 2010)
Keywords: Godin, Gérald; Idéologies; Parti Pris; Édition

''Il y a des chose qu'une personne cultivée ne peut ignorer''- Le Bulletin de la Société d'étude et de conférences (1915-1967): sa genèse, ses actrices et son contenu. - St-Laurent, Fanie (Revue de Bibliothèque et Archives nationale du Québec, 2012)
Keywords: Femmes

Inventaire chronologique des cartes et des plans de Montréal, 1611-1915, avec annotations - Miller, Émile (Rapport annuel du département des archives municipales pour l'année 1915, 1916)
Keywords: Cartes et plans

A Guide to McGill University Calendars for the Academic Years 1853-54 to 1975-76 - Wray, Arpi (Archives de l'Université McGill, 1977)
Keywords: Université McGill

A Preliminary List of the Official Papers of Charles Henry Gould, Record Group 40, Accession 654, Items 1-46, 1895 - Tallman, Julie (Archives de l'Université McGill, 1973)
Keywords: Gould, Charles Henry; Université McGill

Preliminary List of Incoming Letters of McGill Librarian C. H. Gould. Record Group 40, Accession 654, 1901, M-S, Items 1-153 - Stern, Claire (Archives de l'Université McGill, 1977)
Keywords: Gould, Charles Henry; Université McGill

List of Incoming Correspondence of McGill Principal Sir William Peterson, Record Group 2P, Accession 641, Bundles 15-17 - Rubinstein, Renée (Archives de l'Université McGill, 1977)
Keywords: Peterson, William; Université McGill

A Preliminary List of the Incoming Letters of the McGill Librarian Charles H. Gould, Record Group 40, Accession 654/1898, A-C, Items 1-162 - Rooney, Thomas (Archives de l'Université McGill, 1974)
Keywords: Gould, Charles Henry; Université McGill

Répertoire analytique des documents de la Maison de la Trinité de Montréal 1806-1873 - Rabchuk, Gordon; Labelle, Ernest (Archives du Port de Montréal, 1986)
Keywords: Maison de la Trinité; Navigation; Port

A Preliminary Description of Papers Relating to Redpath Museum, Accession 1476 - 1880-1966 - Morgan, Patricia Ann (Archives de l'Université McGill, 1973)
Keywords: Musées; Redpath (musée); Université McGill

Abraham De Sola Papers: A Guide to the Microfilm - Miller, Evelyn (Archives de l'Université McGill, 1970)
Keywords: De Sola, Abraham; Juifs

A Preliminary List of the Incoming Letters of McGill Librarian Charles Henry Gould, 1896, Record Group 40, Accession 654 - Mcleod, Norman (Archives de l'Université McGill, 1974)
Keywords: Gould, Charles Henry; Université McGill

Incoming Correspondence of Sir William Peterson, C.B., Record Group 2P, Accession No. 641, Bundles 3, 4 and 5 - Martyn, Olive M. (Archives de l'Université McGill, 1977)
Keywords: Peterson, William; Université McGill

A Guide to Transcripts of Documents Concerning McGill College and the Royal Institute for the Advancement of Learning, 1842-1849 - King, John (Archives de l'Université McGill, 1977)
Keywords: Royal Institution for the Advancement of Learning; Université McGill

Preliminary List of Incoming Letters of McGill Librarian C. H. Gould, 1899, record group 40, Accession 654 - Dyck, Jacqueline (Archives de l'Université McGill, 1974)
Keywords: Gould, Charles Henry; Université McGill

Preliminary List of Incoming Letters of McGill Librarian C. H. Gould, 1906, O-Z, Record Group 40, Accession 654 - Forget, Gérald (Archives de l'Université McGill, 1977)
Keywords: Gould, Charles Henry; Université McGill

A Preliminary List of the Incoming Correspondence of Sir William Peterson, C.B., Record Group 2 p, Accession 641, Bundles 6A, 7, 8 - Douglas, Lawrence Taylor (Archives de l'Université McGill, 1977)
Keywords: Peterson, William; Université McGill

A Preliminary Description of McGill Teacher Training Records 1888-1938 - Davis, Davena (Archives de l'Université McGill, 1970)
Keywords: Enseignants; Université McGill

A Preliminary Guide to the Files of Principals Sir Arthur Currie 1920-33, A. E. Morgan 1935-37, Lewis William Douglas 1937-39, Record groups 2C, 2N, and 2D, Accession 641 - Alain, Robert (Archives de l'Université McGill, 1974)
Keywords: Currie, Arthur; Douglas, Lewis William; Morgan, A. E.; Université McGill

A Preliminary Guide to the Records of McGill Libraries, Record Group 40 - Alain, Robert (Archives de l'Université McGill, 1973)
Keywords: Université McGill

Inventaire de la Saberdache de Jacques Viger - Ouellet, Fernand (Rapport de l'archiviste de la province de Québec, 1955)
Keywords: Maires; Viger, Jacques

Inventaire des documents et des imprimés concernant la communauté des frères Charon et l'Hôpital Général de Montréal sous le régime français - Massicotte, E.-Z. (Rapport de l'archiviste de la province de Québec, 1923)
Keywords: Charon de La Barre, François; Communautés religieuses; Frères Charon; Hôpital Général; Hôpitaux

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1945)
Keywords: Bourget, Ignace; Évêques

La vie de madame Youville, fondatrice des Soeurs de la Charité à Montréal - Youville, Charles-Marie-Madeleine (Rapport de l'archiviste de la province de Québec, 1924)
Keywords: Communautés religieuses; Dufrost de Lajemmerais, Marie-Marguerite (Youville, Marguerite d'); Hôpital Général; Hôpitaux; Soeurs Grises

Vie de madame d'Youville, fondatrice et première supérieure des Soeurs de la Charité de l'Hôpital Général de Montréal, communément nommées Soeurs Grises, dédiée à cette même communauté - Sattin, Antoine (Rapport de l'archiviste de la province de Québec, 1928)
Keywords: Communautés religieuses; Dufrost de Lajemmerais, Marie-Marguerite (Youville, Marguerite d'); Hôpital Général; Hôpitaux; Soeurs Grises

Inventaire de la correspondance de Mgr J.J. Lartigue - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1942)
Keywords: Lartigue, Jean-Jacques; Évêques

Inventaire de la correspondance de Mgr J.J. Lartigue - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1945)
Keywords: Lartigue, Jean-Jacques; Évêques

Inventaire de la correspondance de Mgr J.J. Lartigue - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1941)
Keywords: Lartigue, Jean-Jacques; Évêques

Inventaire de la correspondance de Mgr J.J. Lartigue - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1943)
Keywords: Lartigue, Jean-Jacques; Évêques

Inventaire de la correspondance de Mgr J.J. Lartigue - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1944)
Keywords: Lartigue, Jean-Jacques; Évêques

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1946)
Keywords: Bourget, Ignace; Évêques

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1955)
Keywords: Bourget, Ignace; Évêques

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1966)
Keywords: Bourget, Ignace; Évêques

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1964)
Keywords: Bourget, Ignace; Évêques

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1965)
Keywords: Bourget, Ignace; Évêques

Correspondance de Mgr Ignace Bourget - Desrosiers, L.-A. (Rapport de l'archiviste de la province de Québec, 1948)
Keywords: Bourget, Ignace; Évêques

L'association loyale de Montréal (Rapport de l'archiviste de la province de Québec, 1948)
Keywords: Association loyale de Montréal

Intimacies in the Neighbourhood: Revisiting Sex Commerce, Families, and Criminal Court Records in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Family and Justice in the Archives. Historical Perspectives on Intimacy and the Law, 2024)
Keywords: Criminalité; Famille; Femmes; Prostitution

Voices of Litigating Women in New France During the Seventeenth and Eighteenth Centuries. - Deslandres, Dominique (Voices in the Legal Archives in the French Colonial World: "The King is Listening", 2021)
Keywords: Autochtones; Esclaves; Femmes; Noirs

Inventaire analytique du fonds Gaspard-Dauth (P5) - Thériault, Monique (Université de Montréal, Service des archives, 1975)
Keywords: Dauth, Gaspard; Université de Montréal

Répertoire numérique détaillé du fonds de l'École ménagère provinciale (E81) - Pélissier, Denise (Université de Montréal, Service des archives, 1979)
Keywords: École ménagère

Inventaire sommaire d'une collection de mandements, lettres pastorales et circulaires de Mgr Jean-Charles Prince (P72) 1846-1886 - Mondou, Céline (Université de Montréal, Service des archives, 1979)
Keywords: Prince, Jean-Charles

Inventaire analytique du fonds Gaspard-Dauth: supplément - Laperle-Dionne, Isabelle; Perron, Hélène (Université de Montréal, Service des archives, 1978)
Keywords: Dauth, Gaspard; Université de Montréal

Etat sommaire du fonds de l'École des Beaux-Arts - Caya, Pierre (Université de Montréal, Service des archives, 1980)
Keywords: École des Beaux-Arts

Correspondance Henry Teuscher - Marie-Victorin, 1932-1944 - Bouchard, André (Archives du Jardin botanique de Montréal, 1978)
Keywords: Jardin botanique; Marie-Victorin, Frère; Teuscher, Henry

Répertoire numérique simple du fonds de l'Association générale des étudiants de l'Université de Montréal - Barriault, Jeannine (Université de Montréal, Service des archives, 1985)
Keywords: Association générale des étudiants de l'Université de Montréal; Université de Montréal; Étudiants

Répertoire numérique du fonds Les-Compagnons-de Saint-Laurent - Bessette, Roger (Archives provinciales, Pères de Sainte-Croix, 1978)
Keywords: Compagnons de Saint-Laurent; Théâtre

Répertoire numérique simple du fonds de l'Institut botanique (Frère Marie-Victorin) - Fournier, Claude (Université de Montréal, Service des archives, 1984)
Keywords: Botanique; Institut botanique; Marie-Victorin, Frère

Trente années d'université, 1914-1944 - Chartier, Émile (Université de Montréal, Service des archives, 1982)
Keywords: Université de Montréal

Répertoire numérique du fonds de l'École de médecine vétérinaire, E57 - Le Berre, Yanick; Jourdain, Claude (Université de Montréal, Division des archives historiques, 1982)
Keywords: Université de Montréal; École de médecine vétérinaire

Répertoire numérique du fonds Serge Garant (P141) - Fillion, Chantale; Metras, Claire (Université de Montréal, Division des archives historiques, 1988)
Keywords: Garant, Serge; Musique

Répertoire des cadres de l'Université de Montréal (1877-1986) - Fillion, Chantale; Jilek, Stanislas (Université de Montréal, Division des archives historiques, 1987)
Keywords: Université de Montréal

Répertoire numérique détaillé du fonds du Secrétariat général, D35, 1876-1950 - Ducharme, Jacques; Pilote, Francine (Université de Montréal, Division des archives historiques, 1981)
Keywords: Université de Montréal

Répertoires numériques simples - Bibliothèque Patrick Allen (A011), Musée commercial et industriel de Montréal (A012) - Ducharme, Daniel (École des hautes études commerciales, Archives historiques, 1987)
Keywords: Allen, Patrick; Musée commercial et industriel de Montréal; École des hautes études commerciales

Répertoire numérique simple du fonds de la Corporation (1957) de l'École des hautes études commerciales (A004), 1957-1972 - Ducharme, Daniel (École des hautes études commerciales, Archives historiques, 1987)
Keywords: École des hautes études commerciales

Répertoire numérique - Corporation de l'École des hautes études commerciales (A001), Corporation des écoles techniques ou professionnelles (A002), Conseil de perfectionnement (A003) - Ducharme, Daniel (École des hautes études commerciales, Archives historiques, 1987)
Keywords: École des hautes études commerciales; École technique

Répertoire numérique du fonds du Secrétariat général (A008), 1957-1971 - Ducharme, Daniel (École des hautes études commerciales, Archives historiques, 1987)
Keywords: École des hautes études commerciales

Répertoire numérique détaillé des dossiers-séance du Conseil pédagogique (A005), 1959-1975 - Ducharme, Daniel (École des hautes études commerciales, Archives historiques, 1988)
Keywords: École des hautes études commerciales

Répertoire numérique détaillé du fonds du Secrétariat général D35, 1951-1972 - Champagne, Michel (Université de Montréal, Division des archives historiques, 1988)
Keywords: Université de Montréal

The Blessed Communion: The Origins and History of the Diocese of Montreal, 1760-1960 - Cooper, John Irwin (Archives' Committee of the Diocese of Montreal, 1960)
Keywords: Anglicans; Diocèse; Protestants

Guide par série et sous-série du fonds Jules-Brunel - Brochu, Frédéric (Université de Montréal, Division des archives historiques, 1988)
Keywords: Botanique; Brunel, Jules

Répertoire numérique simple du fonds de la Société de biologie de Montréal - Pilote, Francine (Université du Québec à Montréal, Service des archives, 1983)
Keywords: Société de biologie de Montréal

Répertoire numérique simple du fonds de l'École normale Jacques-Cartier - Pilote, Francine; Janson, Gilles (Université du Québec à Montréal, Service des archives, 1983)
Keywords: École normale Jacques-Cartier

Répertoire numérique détaillé du fonds du Centre des loisirs Immaculée-Conception - Pilote, Francine; Jeanson, Martine (Université du Québec à Montréal, Service des archives, 1988)
Keywords: Immaculée-Conception (Centre des loisirs)

Répertoire numérique simple du fonds de la Palestre nationale - Janson, Gilles; Charbonneau, Normand (Université du Québec à Montréal, Service des archives, 1988)
Keywords: Palestre nationale

Répertoire numérique détaillé du fonds de la Fédération des écoles normales - Janson, Gilles (Université du Québec à Montréal, Service des archives, 1982)
Keywords: Fédération des écoles normales

Répertoire numérique détaillé du fonds de la Société d'histoire naturelle - Janson, Gilles; Cadieux, Anne-Marie (Université du Québec à Montréal, Service des archives, 1986)
Keywords: Société d'histoire naturelle

Répertoire numérique détaillé du fonds Édouard-Lachapelle - Cadieux, Anne-Marie; Lefrancois, Arlette; Boudreau, Diane (Université du Québec à Montréal, Service des archives, 1984)
Keywords: Lachapelle, Édouard

Répertoire numérique détaillé du fonds du Conseil des arts et manufactures - Cadieux, Anne-Marie (Université du Québec à Montréal, Service des archives, 1984)
Keywords: Conseil des arts et manufactures

Répertoire numérique détaillé du fonds de l'École normale de l'enseignement technique. Supplément - Richard, Nathalie (Université du Québec à Montréal, Service des archives, 1986)
Keywords: École normale de l'enseignement technique

Histoire du Canada - Vachon De Belmont, François (Collection de mémoires et de relations sur l'histoire ancienne du Canada d'après des manuscrits récemment obtenus des Archives et Bureaux Publics en France, 1840)

Histoire de l'eau-de-vie en Canada - Vachon De Belmont, François (Collection de mémoires et de relations sur l'histoire ancienne du Canada, d'après des manuscrits récemment obtenus des Archives et Bureaux Publics en France, 1840)
Keywords: Alcool

Immigrants italiens dans l'espace social et culturel montréalais. Une synthèse historique - Ramirez, Bruno (Histoires d'immigrations à Montréal, 2014)
Keywords: Italiens

Les juifs sépharades à Montréal - Cohen, Yolande (Histoires d'immigrations à Montréal, 2014)
Keywords: Juifs

Un siècle de vie yiddish à Montréal - Anctil, Pierre (Histoires d'immigrations à Montréal, 2014)
Keywords: Juifs

La communauté écossaise de Montréal. Histoire et questions identitaires - Bourbeau, Catherine (Histoires d'immigrations à Montréal, 2014)
Keywords: Écossais

Many Women, Many Voices. Stories from McGill collections - Cooke, Nathalie; Giuliano, Frédéric; Lyons, Christopher; Owens, Gwendolyn; Sundberg, Jacquelyn; Yearl, Mary (Rare and Special Collections, Osler, Art, and Archives of McGill Library, 2018)
Keywords: Femmes; Université McGill

La Gazette littéraire de Montréal 1778-1779 - Doyon, Nova; Cotnam, Jacques (L'archive littéraire au Québec, 2010)
Keywords: Gazette Littéraire de Montréal; Mesplet, Fleury

La guerre de 1812: Journal de Jacques Viger - Viger, Jacques; Andrès, Bernard (L'archive littéraire au Québec, 2012)
Keywords: Maires; Viger, Jacques

Montreal Movies Palaces. Great Theatres of the Golden Era, 1884-1938 - Lanken, Dane (Archives of Canadian Art (& Design), 1993)
Keywords: Cinéma

La Grande Guerre de Paul Caron. Chroniques d'un légionnaire canadien-français (1914-1917) - Richard, Béatrice (L'archive littéraire au Québec, 2015)
Keywords: Guerre

Sans différends, point d'harmonie: repenser la criminalité en Nouvelle-France - Paul, Josianne (Septentrion, 2012)
La lecture des archives judiciaires du Régime français remet en question la vision idéalisée d'une Nouvelle-France où la vie des colons se déroulait tel un long fleuve tranquille. Le quotidien des habitants a été ponctué d'escarmouches survenant au cabaret du coin, de paroles injurieuses prononcées à la clôture contre un voisin négligent, de querelles découlant de la vente d'aliments avariés au marché, de chicanes de ménage et, à l'occasion, de pendaisons sur la place publique. En adoptant une méthodologie située à la croisée de l'histoire et de la criminologie, Josianne Paul a voulu comprendre comment, aux XVIIe et XVIIIe siècles, les habitants de Montréal et l'administration coloniale géraient les situations conflictuelles potentiellement criminalisables. En Nouvelle-France, la justice n'était pas un phénomène purement institutionnel et les colons, de même que l'administration royale, avaient à leur disposition plusieurs modes de résolution de conflit qu'ils savaient manipuler avec doigté afin de résoudre de manière durable leurs différends dans le but de maintenir l'harmonie sociale.
Keywords: Criminalité

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens